The repertory grids method in the investigation of cognitive differentiation in the sphereof communication - T. G. Siroshtanenko (Вестник университета, 2019)
The issue of the selection and use of methods of personal diagnostics, which are individually-oriented, for example, the repertory grids method, have been examined. The possibilities of the method in the diagnostics of cognitive differentiation in the sphere of communication have been studied. Its dignities and advantages have been determined. Practical experience in the development of a repertory lattice has been generalized. The algorithm for filling the grid, the method of calculating the results and determination of cognitive complexity (cognitive simplicity) in the sphere of communication have been presented. The possibilities of the grid in the study of the individual features of communication have been considered.